2020
DOI: 10.1161/strokeaha.119.027268
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Score Including Carotid Plaque Inflammation and Stenosis Severity Improves Identification of Recurrent Stroke

Abstract: Background and Purpose— In randomized trials of symptomatic carotid endarterectomy, only modest benefit occurred in patients with moderate stenosis and important subgroups experienced no benefit. Carotid plaque 18 F-fluorodeoxyglucose uptake on positron emission tomography, reflecting inflammation, independently predicts recurrent stroke. We investigated if a risk score combining stenosis and plaque 18 F-fluorodeoxyglucose would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 22 publications
3
52
0
Order By: Relevance
“…Studies found that plaque inflammation can be noninvasively visualized on positron emission tomography (PET)/CT by increased 18 F-fluorodeoxyglucose ( 18 F-FDG) uptake, and inflammation is more prevalent in the carotid arteries ipsilateral to the recent ischemic event (48). A recent study constructed a risk score (SCAIL [Symptomatic Carotid Atheroma Inflammation Lumen-Stenosis]) based on plaque 18 F-FDG uptake and lumen stenosis, that improved the prediction of early ipsilateral recurrent stroke after correction for established risk factors, even in patients with mild to moderate stenosis (49). FDG PET/CT seemed promising for the detection of inflammation but enables with poor spatial resolution, which impedes simultaneous tracing of other characteristics.…”
Section: Plaque Activitymentioning
confidence: 99%
“…Studies found that plaque inflammation can be noninvasively visualized on positron emission tomography (PET)/CT by increased 18 F-fluorodeoxyglucose ( 18 F-FDG) uptake, and inflammation is more prevalent in the carotid arteries ipsilateral to the recent ischemic event (48). A recent study constructed a risk score (SCAIL [Symptomatic Carotid Atheroma Inflammation Lumen-Stenosis]) based on plaque 18 F-FDG uptake and lumen stenosis, that improved the prediction of early ipsilateral recurrent stroke after correction for established risk factors, even in patients with mild to moderate stenosis (49). FDG PET/CT seemed promising for the detection of inflammation but enables with poor spatial resolution, which impedes simultaneous tracing of other characteristics.…”
Section: Plaque Activitymentioning
confidence: 99%
“… 33 34 The incorporation of 18 F-FDG plaque uptake into a clinical prediction model also improves discrimination of early recurrent stroke, when compared with risk stratification by luminal stenosis alone. 35 Improved methods to identify patients at the highest risk of stroke may refine selection for carotid revascularisation, allowing surgery to be targeted towards patients most likely to benefit. These findings show that plaque inflammation is a clinically important and independent predictor of early stroke recurrence in symptomatic carotid disease.…”
Section: Findings To Datementioning
confidence: 99%
“…Recent studies emphasised the prognostic value of imaging markers other than luminal stenosis of extracranial arteries, including high-risk non-stenotic carotid plaque, 39 calcification 40 or inflammation. 27 Further study using techniques with a higher spatial resolution to detect the composition of plaques or changes of vessel walls would help distinguish the progress of atherosclerosis. Third, the sample size of our subgroup analysis was relatively small due to our special focus based both on symptom duration and DWI positivity, which could result in limited statistical power.…”
Section: Open Accessmentioning
confidence: 99%